If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-s+2s-3=4
We move all terms to the left:
-s+2s-3-(4)=0
We add all the numbers together, and all the variables
s-7=0
We move all terms containing s to the left, all other terms to the right
s=7
| (–9+5t)(–6)= | | 2(x–8)=–22 | | 20/8=x/16 | | (4x-18)+(3x+4)=180 | | 1.20x+3.60=9.6 | | 12/8=x/12 | | -156=12x | | 2x=5=13 | | -11+5n=5+7n | | 4g+4g=16 | | 5x/3+13=-2 | | -5x+4=-x+16 | | 2x+16=5x-17=11x | | 181=-y+102 | | 2x+14.5=21.5 | | -4x-8x=-144 | | -4n+9=+4n+9 | | 0.29x-7.34=1.64+0.79x | | -49x+8)-11=3-26 | | 2x+3−5x=3 | | (27)3^2-2*3+u=(3^3-3*8)(2)+u | | -4n+9=-4n+9 | | 2x+16=5x-17=11 | | g-2/4=-3 | | 2+6a-6a=3a+2-6 | | 7x+2=–3x–5 | | 7(8-8y)+10=-270 | | x/42=15/35 | | -14=p11 | | -4n+9=+-4n+9 | | 4z-6=6(z+2)=8 | | -4x+3(5x+10)=36 |